Ніщо як Усе: на перехресті традиційного Сходу й авангардного Заходу - Більченко, Євгенія; Bilchenko, Yevheniya (Східноєвропейський національний університет імені Лесі Українки, 2014)
Стаття присвячена культурологічному аналізу поняття Ніщо в контексті діалогу традиційної східної онтології та некласичної естетики Заходу. Головна позиція статті – розуміння Ніщо не як тотальної негації, а як абсолютної повноти буття, що виражається, зокрема, через містичний стан «саторі» у дзен та філософські категорії свободи, іронії та еросу в естетиці авангарду і постмодерну. Неомодерну версію Ніщо як Третього (підтексту), що врівноважує стосунки Я (Автора-творця) та Іншого (Читача), надає філософія діалогу. Article is devoted to culturological analysis categories of Nothing, prototype of which is originated in the traditional cultures of the East as an archetype of emptiness (silence, sacred silence, enlightenment). The author exposes a critical understanding of classical modernist painting of the Western world (logocentrism), where Nothing was associated exclusively with the total negation, lack of attributes of life − and makes an attempt to fill the ontological semantics of Nothing by positive value creation of new forms of art in the Avant-garde and postmodern. To achieve this goal, the author refers to the interpretation Nothing like a point of convergence of minima and maxima in the state of sacred silence “satori” inherent in the culture of Zen, where time loses its duration and the space − the length. Currently, this becomes an absolute currently, includes also a past and a future. Familiarity with Eastern culture in the Western world of the twentieth century (in particular, the English translation of texts D. Suzuki) leads to the construction of new metaphysical reality, based on the experience of the sacred Nothing in particular − kubofuturizm. Nothing is transformed in accordance with Western demands to compensate for the “crisis of history” − into a transcendental selfness of the artist-creator. It embodies the idea of a radical deconstruction of artistic and aesthetic forms for output to the level of some of the initial, basic, original form, which has an absolute ontological content. Nothing like the premise of Total (fullness of life) is realized through the philosophical and aesthetic categories of freedom, irony and Eros, which the author defines as the basic concepts of non-classical cultural identity of the West, facing the Orientalism. Involuntary transformation of Nothing like freedom, irony and Eros in their distorted forms and the associated with it spread of kitsch, masking as a postmodern “double code” leads us to the need for a new culturological concept of Nothing, possible. in the opinion of the author’s work in the context of the philosophy of dialogue in its neomodern version, where freedom is combined with the responsibility of the creative subject, the irony − with finesse, Eros − with morality, that is − modern − with the postmodern. Border transcultural status of Nothing disclosed in the context of the philosophy of dialogue as a figure of the Third − intermediary in dialogue of Ego and Other, leading to a gradual transformation (spirituality, humanization, ontologization) of Alien image, which appears in the eyes of the creator as an imoge of society − in the way of the Middle. Ligament between the figure of the Third philosophy of dialogue and concept Nothing is realized through internal (internalized) understanding of the Third as the “unspoken” or subtext of the text in the theory of intertextuality. The author concludes that the dialogue between the West and the East on the basis of ontological understanding of absolute being of Nothing will allow, on the one hand, − to overcome the identity crisis, that emerged in the West after the collapse of projects simultaneously modern and postmodern, − and on the other hand − to bring non-classical aesthetic individuality to the level of dialogue and between Ego and Other.
Nothing like All: at the Crossroads of the Traditional East and the Avant-garde West
Keywords: Ніщо; Nothing; саторі; satori; свобода; freedom; іронія; irony; ерос; Eros; авангард; avant-garde; постмодерн; postmodern; Третій; Third; підтекст; the subtext; філософія діалогу; the philosophy of dialogue; неомодерн; neomodern